Biotechnological strategies and tools for Plum pox virus resistance: trans-, intra-, cis-genesis, and beyond - Ilardi, Vincenza; Tavazza, Mario (Frontiers in Plant Science, 2015)
Plum pox virus (PPV) is the etiological agent of sharka, the most devastating and economically important viral disease affecting Prunus species. It is widespread in most stone fruits producing countries even though eradication and quarantine programs are in place. The development of resistant cultivars and rootstocks remains the most ecologically and economically suitable approach to achieve long-term control of sharka disease. However, the few PPV resistance genetic resources found in Prunus germplasm along with some intrinsic biological features of stone fruit trees pose limits for efficient and fast breeding programmes. This review focuses on an array of biotechnological strategies and tools, which have been used, or may be exploited to confer PPV resistance. A considerable number of scientific studies clearly indicate that robust and predictable resistance can be achieved by transforming plant species with constructs encoding intron-spliced hairpin RNAs homologous to conserved regions of the PPV genome. In addition, we discuss how recent advances in our understanding of PPV biology can be profitably exploited to develop viral interference strategies. In particular, genetic manipulation of host genes by which PPV accomplishes its infection cycle already permits the creation of intragenic resistant plants. Finally, we review the emerging genome editing technologies based on ZFN, TALEN and CRISPR/Cas9 engineered nucleases and how the knockout of host susceptibility genes will open up next generation of PPV resistant plants.